The Process of Leaving Abuse: Midlife and Older Male Experiences of Female-Perpetrated Intimate Partner Violence - Carthy, Nikki (Journal of interpersonal violence, 2023)
Leaving an abusive relationship is a difficult process for all survivors. For men, this can be particularly challenging due to the current knowledge and support for survivors being heavily influenced by a feminist discourse, despite a growing body of research that examines men’s experiences. This raises concerns about how men make sense of abuse, where they seek support for injuries and psychological distress, and what services are available to them to help them move on from abuse. Narrative interviews with 12 midlife and older men (aged 45–65 years) who had experienced intimate partner violence from a female were conducted with the aim to explore their journey of leaving abuse. The men’s stories revealed themes of how they made sense of what was happening to them (legitimacy as a survivor and self-help), their experiences of service readiness to respond to male victimization (discrimination from police, legal system set up to support women, and service readiness for males), and how men can leave abuse (post-separation abuse and support from friends and family). Implications of the findings demonstrate that many services are still not equipped to support male survivors. The men in our study found it difficult to comprehend their experience as abuse and this is negatively reinforced by ineffective services and stereotypical beliefs about abuse. However, informal support through friends and family is a powerful tool in supporting men to leave abusive relationships. More work is needed to increase awareness of male survivors and ensure that services, including legal systems, are inclusive.